Changes over time in language learning strategy use by foreign language learners. Issue 2 (3rd April 2021) - Lancho Perea, Luis Andrés
Abstract: This study explores the reported changes over time of the use of language learning strategies based on periodic self-reports of undergraduates that studied Spanish as a foreign language for three years. The purpose was to gain a better understanding of how the use of particular strategies evolved and consolidated or disappeared as students became progressively more proficient in Spanish. By using Oxford's taxonomy that differentiates and classifies language learning strategies according to their function, and employing a mixed-method approach that combined successive administrations of Oxford's Strategy Inventory of Language Learning with in-depth interviews, this study found that the most frequently used strategies as reported by students who started as absolute beginners and continued studying Spanish for three consecutive years were metacognitive strategies in the first year, social strategies in the second year and cognitive strategies in the third year. This study analysed and discussed these findings.